THE EFFECT OF KEEPING VOCABULARY NOTEBOOK ON STUDENTS’ VOCABULARY ACHIEVEMENT AT THE SECOND GRADES IN SMP N 2 RAHA - Nuur, Mauliddin; Tambunan, Tambunan; Nurnia, Nurnia (Journal of Teaching of English, 2019)
This study investigated the effect of keeping vocabulary notebooks on students’ vocabulary achievement at the second grade in SMPN 2 Raha. The purpose of this study is to find out a significant effect after keeping vocabulary notebook  on  students’  vocabulary  achievement.  This study applied quantitative research design. This study used vocabulary notebook as a treatment in learning process for the students. The subject of this study was second grades students of SMPN 2 Raha who were registered in academy year 2017-2018. The technique of taking sample of study was purposive sampling. The sample of this study was class VIII2  as an experimental class and class VIII1  as a control class. The instrument of this study was vocabulary test consist of 30 numbers, the result showed that there was not a significant effect of keeping vocabulary notebooks on students’ vocabulary . It was not proved with the improvement of students were the students more active in the classroom rather than the teacher. Students can discover the new words by themselves on the learning activities. the result of students’ vocabulary test was supported with the mean score in post-test of experimental class is higher than the mean score in the post-test of control class. The mean score for the post-test in experimental class was 82.15 and the mean score for post-test in control class was 79.36. but the data was not distributed normally, the analysis of the data was used the non parametric analysis and the result of Mann Whitney non parametric analysis, the value of Sig  2-tailed  =  0.57  with  α  0.05.  it  means  that  H0   is accepted. It is because the value of Asymp sig 2-tailed is above the alpha (a) value. This result showed that there was not a significant effect of using vocabulary notebooks on   students’   vocabularu   achievement   at   the   second grades in SMP Negeri 2 Raha. Keywords: Effect,Vocabulary Notebooks,Learning Activities,Vocabulary Achievement.